Ensemble Machine Learning to Detect Sarcasm in English on Twitter Social Media - Rosid, Mochamad Alfan; Sambada, Muhammad Arginanta Kafi; Busono, Suhendro; Muharram, Fajar (Journal of INISTA, 2023)
Detecting sarcasm in English tweets on social media platforms like Twitter is a complex task due to its subtle and ambiguous nature. This study explores the use of ensemble machine learning techniques, including Logistic Regression, Naive Bayes, Decision Tree, and Support Vector Machine (SVM), to effectively identify sarcasm. A dataset containing sarcastic and non-sarcastic English tweets was collected and preprocessed. Features representing lexical, syntactic, and semantic information were extracted to train and evaluate the ensemble models. The Support Vector Machine method demonstrated the highest performance among the techniques employed, achieving an accuracy of 80% and an F1-score of 80% for sarcasm detection. This highlights the efficacy of Support Vector Machines in capturing complex patterns and differentiating between sarcastic and non-sarcastic tweets. By leveraging the strengths of multiple machine learning algorithms, the ensemble approach enhances the overall performance of the sarcasm detection system. It provides a more robust and accurate detection of sarcasm, thereby improving the understanding of user sentiments and opinions in online conversations. This research contributes to sentiment analysis and natural language processing, offering valuable insights into sarcasm detection in social media. The findings have practical implications for interpreting user-generated content on platforms like Twitter, enabling a better understanding of user sentiments and facilitating more meaningful interactions.